HFE mutations in patients with hereditary haemochromatosis in Sweden - Cardoso, E. (2010)
OBJECTIVE: To determine the frequency of mutations (C282Y and H63D) in a newly identified gene HFE in patients with hereditary haemochromatosis (HH) in Sweden. DESIGN: Molecular genetic analyses of the HFE gene (polymerase chain reaction (PCR) followed by enzyme restriction) were performed in genomic DNA from unrelated patients with a clinical diagnosis of HH and in healthy subjects. SETTINGS: Patients with HH treated with phlebotomies at Karolinska Hospital and Huddinge Hospital were analyzed. SUBJECTS: Eighty-seven unrelated patients with HH and 117 healthy controls. RESULTS: It was found that the HFE C282Y mutation occurs in 94.2% of chromosomes from patients with HH. Eighty patients (92.0%) were homozygous for the C282Y mutation and one was heterozygous. Three patients were heterozygous for both C282Y and H63D mutations. One patient was homozygous and one was heterozygous for the H63D mutation. One patient carried normal alleles. In healthy controls, the C282Y mutation occurred in nine subjects (7.7%), all of which were heterozygous. The H63D mutation was found in 28 control subjects, one of which was homozygous. CONCLUSIONS: We found that the majority of patients with HH have the C282Y mutation in the HFE gene. The frequency of the H63D mutation was higher in controls than in patients with HH, although in chromosomes at risk the frequency of the H63D mutation was higher in patients.